(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2012)
It would be difficult to situate cinema, in the sense of institutional cinema, in a chart whose purpose would be to illustrate the various allographic and autographic aspects (in the sense Goodman and Genette use these terms) of different art forms. Cinema is a complex art in which, like in a rhizome, various expressive means, channels of transmission, systems of notation and modes of execution overlap. The task is even bigger with respect to the body of films known as early cinema, or rather kine-attractography. Early cinema is a hundred times more rhizome-like than institutional cinema, because it involves a number of “performative” gestures (live music or commentary, etc.) whose effect is to multiply the sites of creation or authorship. Kine-attractography involves both allographic recording (because it is purely instrumental) and the autographic performance of a given actor, even though anonymous, in an execution-screening complemented by equally autographic performances by live figures. Hence, the difficulty in identifying the underlying system joining the various instances at work in such situations. Just as photography rhymes with allography, cinema is a photo- graphic art before it is an autographic one.